The tracked society: Interdisciplinary approaches on online tracking. (November 2020) - König, René; Uphues, Steffen; Vogt, Verena; Kolany-Raiser, Barbara
Online tracking in its various forms is a backbone of digitalization that has sparked hopes and fears alike: It opens up new opportunities for users and businesses as it enables individually targeted content. At the same time, the encompassing tracking of often unaware and ill-informed users and the opaque practices of data procession has alarmed critics from multiple sides. How can we better understand but also proactively and constructively shape the emerging Tracked Society? Our special issues seek to shed light on these questions from various perspectives and disciplines. In this introduction, we give a brief overview of the topic in general and our special issue in particular.